THE INFLUENCE OF LEMON AROMATHERAPY AND SEFT ON ANXIETY LEVELS OF POST PARTUM AT ARSY MEDIKA CLINIC - Tonasih Tonasih; Vianty Mutya Sari; Wiwin Widayanti; Euis Merlinda (Jurnal Smart Kebidanan, 2025)
Psychological disorders during post partum include post partum blues to post partum depression. Early signs of post partum depression include anxiety and worry about the baby.Objective: to determine the effect of Lemon Aromatherapy and SEFTon the anxiety level of Post partum Mothers. Method: quasi-experimental research design using one group pretest-posttest design. The sample was 30 post partum mothers who experienced anxiety at the Pratama Arsy Medika Clinic. Data collection used the HARS questionnaire. Data analysis was univariate and bivariate (Wilcoxon Signed Rank Test). The average anxiety levelbefore the intervention was 11.57 (Standard Deviation = 8.99 3). The median anxiety level was 11.50 and the mode was 1. The lowest anxiety level was 0, the highestwas 30 with a range of 30. The average anxiety level after the intervention was 5.63 (Standard Deviation = 5.096). The mediananxiety level is 4.00 and the mode is 3. The lowest anxiety level is 0, the highest is 18 with a range of 18. The combination therapy of Lemon Aromatherapy and SEFT has a significant effect in reducing anxiety. It is hoped that midwives will apply Lemon Aromatherapy and SEFT to reduce anxiety in post partum mothers.